Using integrated control methodology to optimize energy performance for the guest rooms in UAE hospitality sector. (5th May 2016) - AlFaris, Fadi; Abu-Hijleh, Bassam; Abdul-Ameer, Alaa
Highlights: Energy efficiency in 4 and 5 star luxury hotels in the United Arab Emirates. The normalized energy use index (EUI) ranges between 241.5 and 348.4 kWh/m 2 /year for post 2003 hotels. The normalized energy use index (EUI) ranges between 348.4 and 511.1 kWh/m 2 /year for pre 2003 hotels. Integrated HVAC and lighting control strategies can reduce total energy consumption by up to 31.5%. Abstract: The hospitality sector is growing rapidly in the UAE and especially in Dubai. As a result, it contributes substantially in the UAE's carbon footprint. This research was conducted to measure, evaluate and increase the energy efficiency in 4 and 5 star luxury hotels in UAE. Energy benchmarking analysis was used to analyze the energy data of 19 hotel buildings to differentiate between usual and best practice of energy performance. Moreover, the normalized energy use index (EUI) kWh/m 2 /year has been identified for the best, usual and poor practice hotels. It was found that the normalized EUI ranges between 241.5 kWh/m 2 /year or less as a best practice to more than 361.3 kWh/m 2 /year of the poor energy practice for the hotels constructed after the year of 2003. Whereas the hotels' energy data showed higher values for those constructed before 2003, as the normalized EUI varies between 348.4 kWh/m 2 /year as best practice to more than 511.1 kWh/m 2 /year. An integrated control strategy has been employed to improve the energy performance and assess the energy saving for the guestroom. This technique showed that the overall energy performance improvement reached to 31.5% out of entire energy consumption of the hotel including electricity and gas. This reduction resulted in 43.2% savings from the cooling system and 13.2% from the lighting system due to the installing of the integrated control system in the guestrooms.